The number of the heavens a history of the multiverse and the quest to understand the cosmos - Siegfried, Tom, 1950- (Harvard University Press, 2019)
"One of the most controversial, cutting-edge ideas in cosmology-the possibility that there exist multiple parallel universes-in fact has a long history. Tom Siegfried reminds us that the size and number of the heavens have been contested since ancient times. His story offers deep lessons about the nature of science and the quest for understanding"--